Prevalence and correlates of men’s and women’s alcohol use in agrarian, trading and fishing communities in Rakai, Uganda - Wagman, Jennifer A.; Nabukalu, Dorean; Miller, Amanda P.; Wawer, Maria J.; Ssekubugu, Robert; Nakowooya, Hadijja; Nantume, Betty; Park, Eunhee; Hahn, Judith A.; Serwadda, David M.; Sewankambo, Nelson K.; Nalugoda, Fred; et al. (PLoS ONE, 2020)
Uganda has one of the highest rates of alcohol use in sub-Saharan Africa but prevalence and correlates of drinking are undocumented in the Rakai region, one of the earliest epicenters of the HIV/AIDS epidemic in East Africa. Methods We analyzed cross-sectional data from 18,700 persons (8,690 men, 10,010 women) aged 15–49 years, living in agrarian, trading and fishing communities and participating in the Rakai Community Cohort Study (RCCS) between March 2015 and September 2016. Logistic regression models assessed associations between past year alcohol use and sociodemographic characteristics, other drug use and HIV status, controlling for age, religion, education, occupation, marital status, and household socioeconomic status. Results Past year alcohol prevalence was 45%. Odds of drinking were significantly higher in men (versus women) and fishing communities (versus agrarian areas). Odds of drinking increased with age, previous (versus current) marriage and past year drug use. By occupation, highest odds of drinking were among fishermen and (in women) bar/restaurant workers. Alcohol-related consequences were more commonly reported by male (vs. females) drinkers, among whom up to 35% reported alcohol dependence symptoms (e.g., unsteady gait). HIV status was strongly associated with alcohol use in unadjusted but not adjusted models. Conclusions Alcohol use differed by gender, community type and occupation. Being male, living in a fishing community and working as a fisherman or restaurant/bar worker (among women) were associated with higher odds of drinking. Alcohol reduction programs should be implemented in Uganda’s fishing communities and among people working in high risk occupations (e.g., fishermen and restaurant/bar workers).
Keywords: Men’s and women’s alcohol use; Agrarian; Trading and fishing communities; Uganda